Associations of circadian eating pattern and diet quality with substantial postpartum weight retention - Loy, See Ling (2020)
Besides food quantity and quality, food timing and frequency may contribute to weight regulation. It is unclear if these factors during pregnancy can influence maternal weight retention after childbirth. We thus aimed to examine the associations of maternal circadian eating pattern and diet quality in pregnancy with substantial postpartum weight retention (PPWR) at 18 months in an Asian cohort. We assessed circadian eating pattern and diet quality of 687 women using 24-h dietary recalls at 26-28 weeks' gestation. We calculated PPWR by subtracting maternal weight in the first trimester from weight at 18-month postpartum and defined substantial PPWR as ≥5 kg weight retention. Multivariable binary logistic regression was performed. Overall, 16% of women had substantial PPWR. After the confounders adjustment, night eating, defined by greater night-time caloric intake (odds ratio 1.95; 95% confidence interval 1.05, 3.62), and lower diet quality, classified by median score of the Healthy Eating Index (1.91; 1.17, 3.10), were independently associated with higher odds of substantial PPWR. No associations with substantial PPWR were observed for night fasting duration and number of eating episodes. In conclusion, alignment of eating time with day-night cycles and diet quality during pregnancy may play a role in PPWR, with possible implications for long-term obesity risk.